A Confirmed Case of Toxic Shock Syndrome Associated with the Use of a Menstrual Cup - Michael A Mitchell; Steve Bisch; Shannon Arntfield; Seyed M Hosseini-Moghaddam (Canadian Journal of Infectious Diseases and Medical Microbiology)
Menstrual cups have been reported to be an acceptable substitute for tampons. These flexible cups have also been reported to provide a sustainable solution to menstrual management, with modest cost savings and no significant health risk.